E-Tailing Market Scenario in India - A Bird’s Eye View - Muthamizh Vendan Murugavel, D. (Indian Journal of Marketing, 2010)
Electronic retailing, most commonly known as E-tailing, is nothing but shopping through the Internet and other media forms. E-tailing is "retailing conducted online, over the internet". E-tailing is synonymous with business-to-consumer (B2C) transactions. E-retailing comes under e-commerce. E-tailing helps retailers to build loyal customers and is aimed at selling in areas where they do not have a physical presence. E-commerce and E-tailing, from a business perspective, offer an opportunity to cater to consumers across geographies, with no operational timings, unlimited shelf space - and all this with miniscule quantity of infrastructure. Most growth drivers are in India’s favour - demographics, economy, changing lifestyle, exposure to new ideas. There is no doubt that India is moving towards broadband, and is experiencing strong growth in Web-based sales.The increase in the PC and internet penetration along with the growing preference of Indian consumers to shop online has given a tremendous boost to e-tailing - the online version of retail shopping. An estimated 10 per cent of the total e-commerce market is accounted by e-tailing. With the progress made on e-commerce, various corporations selling different products and services considered setting up e-stores on the Internet to bring more customers closer to them. In fact, there has been a continuous rise in the number of people accessing the Internet. According to online research and advisory firm Juxt Consult’s ’India Online’ 2008, there are over 49 million internet users in India. Significantly, internet penetration (as a percentage of population) has grown to 12 per cent, up 3 per cent from last year’s 9 per cent. Today, as Indians are making online purchases like never before, both the number and variety of products sold online has grown exponentially. More and more retailers are starting to realize the benefits of e-tailing.